2012
DOI: 10.1128/aac.05798-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clarithromycin in Inflammatory Markers of Patients with Ventilator-Associated Pneumonia and Sepsis Caused by Gram-Negative Bacteria: Results from a Randomized Clinical Study

Abstract: dOne recent, double-blind, randomized clinical trial with 200 patients showed that clarithromycin administered intravenously for 3 days in patients with ventilator-associated pneumonia (VAP) accelerated the resolution of pneumonia and decreased the risk of death from septic shock and multiple organ dysfunctions (MODS). The present study focused on the effect of clarithromycin on markers of inflammation in these patients. Blood was drawn immediately before the administration of the allocated treatment and on si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 18 publications
(20 reference statements)
2
36
0
1
Order By: Relevance
“…In addition, macrolides have been shown to inhibit biofilm formation and decrease mucus hypersecretion, leading to improved mucociliary clearance (51). Furthermore, in a recent study in critically ill patients with ventilator-associated pneumonia (53), treatment with clarithromycin restored the balance between pro-and anti-inflammatory mediators in patients with sepsis. Furthermore, in a recent study in critically ill patients with ventilator-associated pneumonia (53), treatment with clarithromycin restored the balance between pro-and anti-inflammatory mediators in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, macrolides have been shown to inhibit biofilm formation and decrease mucus hypersecretion, leading to improved mucociliary clearance (51). Furthermore, in a recent study in critically ill patients with ventilator-associated pneumonia (53), treatment with clarithromycin restored the balance between pro-and anti-inflammatory mediators in patients with sepsis. Furthermore, in a recent study in critically ill patients with ventilator-associated pneumonia (53), treatment with clarithromycin restored the balance between pro-and anti-inflammatory mediators in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors measured markers of inflammation (serum IL-10, TNF-alpha, as well as the expression of various cytokines in stimulation assays) and apoptosis at baseline and for 6 days following treatment [41]. They found that treatment with clarithromycin restored the balance between proinflammatory versus anti-inflammatory mediators, resulted in more efficient antigen presentation, and increased apoptosis.…”
Section: Immune Modulationmentioning
confidence: 95%
“…Furthermore, our cohort was mainly comprised of severe sepsis patients without pneumonia and we identified a beneficial outcome from azithromycin use in these patients as well, which few studies have previously reported. A trend for diminished number of days requiring ventilator support was also observed, potentially limited by sample size and high variability, as other studies have shown shorter times to successful discontinuation of mechanical ventilation with a macrolide in severe sepsis patients [26]. Further investigations are warranted to clarify the association of macrolide use on clinical outcomes in different phenotypes of critically ill patients, especially severe sepsis patients without pneumonia.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, more randomized controlled trials (RCTs) have investigated outcomes from macrolide use in severe sepsis, specifically in patients with ventilator-associated pneumonia, but clinical equipoise remains in clinical trials. For example, one recent RCT found no mortality benefit in patients with gram-negative sepsis treated with clarithromycin [14], while another study of severe sepsis patients with ventilator-associated pneumonia reported decreased risk of death from septic shock and multiple organ dysfunctions associated with the same agent [26]. Our study in severe sepsis patients found that early use of azithromycin for at least 48 hours, independent of other risk factors and accounting for organ dysfunction and presence of shock, was associated with six more days free of ICU care compared to the group not receiving azithromycin.…”
Section: Discussionmentioning
confidence: 99%